2014
DOI: 10.1016/j.compstruct.2013.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically coupled laminates with balanced plain weave

Abstract: Definitive listings of laminate stacking sequences are derived for balanced plain weave 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 2 laminate class is shown to give rise to seven unique forms of coupled laminate through judicious off-axis orientation. Invariant off-axis properties are also identified in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…6(b) reveal that when the laminate aspect ratio a/b > 1, 8-14 plies A F B 0 D S laminates with immunity to HTSD, except 13-ply A F B 0 D S laminates with immunity to HTSD, all fall on or below the buckling strength of the equivalent FIL. The buckling strengths for 8,9,10,11,12,14 plies A F B 0 D S laminates with immunity to HTSD are shown to be up to 27.7% lower than the equivalent FIL, while the buckling strength for13-ply A F B 0 D S laminates with immunity to HTSD is shown to be up to 18.3% higher than the equivalent FIL.…”
Section: Comparisonmentioning
confidence: 89%
See 1 more Smart Citation
“…6(b) reveal that when the laminate aspect ratio a/b > 1, 8-14 plies A F B 0 D S laminates with immunity to HTSD, except 13-ply A F B 0 D S laminates with immunity to HTSD, all fall on or below the buckling strength of the equivalent FIL. The buckling strengths for 8,9,10,11,12,14 plies A F B 0 D S laminates with immunity to HTSD are shown to be up to 27.7% lower than the equivalent FIL, while the buckling strength for13-ply A F B 0 D S laminates with immunity to HTSD is shown to be up to 18.3% higher than the equivalent FIL.…”
Section: Comparisonmentioning
confidence: 89%
“…It insures the laminate is immune to thermal warping distortion which occurs on cooling after the elevated temperature curing process used in the manufacture [8]. However, it is noted that the hygro-thermally curvature-stable laminates do not guarantee hygro-thermal curvature stability when the laminates are introduced into structure configuration.…”
Section: Introductionmentioning
confidence: 99%
“…As seen in the UD laminate sequences of Fig Single ply terminations applied to NCF materials are equivalent to two adjacent ply terminations in traditional UD materials [21] and therefore introduce a constraint that reduces the design space substantially in contrast to a general two ply termination scheme [22], particularly in 'thin laminate' designs. However, this can be overcome by adopting 'thin-ply' or 'spread-tow' technology, which will allow an exponential increase in tailoring opportunities by bringing design flexibilities, found only in traditionally thick laminate construction, into the thin laminate domain.…”
Section: Bi-angle Non-crimp Fabric Hybrid Laminatesmentioning
confidence: 99%
“…Ply terminations can also be applied to any layer without 3 changing the Extension-Shearing and Bending-Twisting dominant mechanical coupling, necessary for aero-elastic tailoring of wing-box structures. However, thermal warping distortions are eliminated only when the number of repeats (r) remain large.Recent research has however demonstrated that tailored Non-Crimp Fabric (NCF) designs, based on 0/45 and 0/-45 architectures, can produce fully uncoupled laminates or laminates with Extension-Shearing and/or Bending-Twisting coupling, and that all have immunity to thermal warping distortion [7]. The extent to which tapered laminate designs can be achieved, without introducing unwanted thermo-mechanical coupling, was also investigated through a layer termination algorithm to introduce single-layer [8] or, where necessary, multiple-layer terminations [4,7].…”
mentioning
confidence: 99%
“…However, thermal warping distortions are eliminated only when the number of repeats (r) remain large.Recent research has however demonstrated that tailored Non-Crimp Fabric (NCF) designs, based on 0/45 and 0/-45 architectures, can produce fully uncoupled laminates or laminates with Extension-Shearing and/or Bending-Twisting coupling, and that all have immunity to thermal warping distortion [7]. The extent to which tapered laminate designs can be achieved, without introducing unwanted thermo-mechanical coupling, was also investigated through a layer termination algorithm to introduce single-layer [8] or, where necessary, multiple-layer terminations [4,7]. This research followed related studies on laminate design for uni-directional (UD) fibre architectures for fully uncoupled laminates [9], and those with Extension-Shearing [10] and/or Bending-Twisting coupling [11,12].The results presented in this article investigate these four laminate classes constructed from the new NCF architectures, see Fig.…”
mentioning
confidence: 99%